Effects of Dietary Green Microalgae (Chlorella vulgaris) and Iron Nanoparticles on Biochemical, Enzymatic, and Tissue Health in Cyprinus carpio - Basim. S. A Al Sulivany; Ivan Omar; Alan Yousif; Muhammad Owais (Airlangga University, 2025)
This study investigates the effects of Chlorella vulgaris and iron nanoparticles (Fe-NPs) as dietary supplements on the health of Cyprinus carpio. Eighty juvenile carp (156.8 ± 2.14 g) were divided into four groups: control (T0), 10% C. vulgaris (T1), 85 mg/kg Fe-NPs (T2), and a combination of both (T3), fed for 60 days. Biochemical, enzymatic, and histological parameters were analysed. The results showed that C. vulgaris supplementation (T1) provided the most significant benefits by reducing glucose levels. The combination group (T3) also showed improved glucose regulation. Serum ALT and AST were lowest in T3, while T1 showed muscle enzyme reduction (ALT: 50.53 ± 2.49 U/l; AST: 596.1 ± 88.15 U/l). Histologically, T1 enhanced muscle fibre density and spleen immune activity, whereas T3 mitigated Fe-NPs-induced iron accumulation. In conclusion, while all treatments improved fish health, C. vulgaris alone offered the most consistent metabolic, enzymatic, and tissue benefits, highlighting its potential as a sustainable aquaculture feed additive.